Barbados. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Barbados during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, food safety, family farming, agribusiness, horticulture, agricultural schools, training, protected agriculture, management of crops, inclusion of young people and in the control of plant diseases.